2015
DOI: 10.1016/j.jrras.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the role of α-lipoic acid against the oxidative stress of induced iron overload

Abstract: Available online xxx keywords: Lipoic acid Iron overload MDA EPR TIBC Osmotic fragility Hemoglobin absorption spectrum a b s t r a c tThis work was aimed to study the protective role of a-lipoic acid against the oxidative damage of induced iron overload. Iron (Fe) overload is a complication of the treatment, by chronic transfusion, of a number of genetic diseases associated with inadequate red cell production (anemias) and of other genetic diseases that lead to excessive iron absorption from the diet. Male rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Interestingly, ALA is able to act inside the lysosomes, the conjugated action of cysteine and acid pH favors the rapid reduction of ALA in DHLA, possibly with the help of the lysosomal constituent, such as the lysosomal thiol reductase. Through its two vicinal thiolic groups, DHLA forms a Table 2:4 complex with Fe III (Fe 2 [DHLA] 4 ), and a less stable one with Fe II [27,28,29,30,31,32,33]. Several groups have reported that lysosomal degradation of ferritin is crucial for the utilization of ferritin iron stores in a number of different settings and plays a central role in iron extraction from ferritin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ALA is able to act inside the lysosomes, the conjugated action of cysteine and acid pH favors the rapid reduction of ALA in DHLA, possibly with the help of the lysosomal constituent, such as the lysosomal thiol reductase. Through its two vicinal thiolic groups, DHLA forms a Table 2:4 complex with Fe III (Fe 2 [DHLA] 4 ), and a less stable one with Fe II [27,28,29,30,31,32,33]. Several groups have reported that lysosomal degradation of ferritin is crucial for the utilization of ferritin iron stores in a number of different settings and plays a central role in iron extraction from ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 20 µg/mL solution of acridine orange in appropriate buffer were added to100 µL of cell suspension and incubated at room temperature for 20 min. Finally, the appropriate isotopic control was also included and labeled cells were acquired using a Beckman Coulter FC-500 flow cytometer [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Mean plasma half-life of α-lipoic acid is approximately 30 min following both intravenous (iv) or oral administration [ 261 ]. Ali et al (2015) reported that administration of α-lipoic acid leads to a decrease in the level of lipid peroxidation in plasma, liver, and brain [ 262 ]. This property may be attributed to its bioavailability, which it employs in counteracting oxidative species directly.…”
Section: Counteractive Antioxidant Defencementioning
confidence: 99%
“…79 It is involved in the reduction of Fe 3+ to Fe 2+ and may help prevent iron overload associated toxicity. 80 Treatment with lipoic acid decreased brain atrophy as measured by the percent change in brain volume in SPMS patients. 39 However, all other CNS imaging associated and clinical measures failed to show significant benefits, but may stem from lack of power due to the small sample size.…”
Section: Moving Forwardmentioning
confidence: 99%